Male accessory gland inflammation (MAGI): an evolving entity. (September 2022) - Noweir, Hosam A.; Modgil, Vaibhav; Pearce, Ian
Male accessory gland infection (MAGI) is a generic acronym indicating inflammatory conditions affecting the prostate gland, seminal vesicles, the ductus deferens and the epididymis. It is a frequent disease, mostly with a chronic course. Majority of the MAGIs remain asymptomatic, thereby leading to a debate whether to treat these patients or not. The primary criterion for MAGI was suggested by Comhaire and colleagues in 1980. The role of MAGI in causing infertility and sexual dysfunctions has long been a matter of debate. The most recent studies show that MAGI could alter, with various mechanisms, both conventional and biofunctional sperm parameters, and determine worst reproductive outcome. This article provides an overview of up-to-date research findings about MAGI with special focus on data published on its impact on fertility; and diagnostic criteria including cellular and seminal biomarkers along with the promising results of emerging proteomic platforms for the identification of MAGI.